Rozbor efektivnosti podnikatelského projektu - Nábělek, Marek (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Bakalářská práce se zabývá investicí do realizace smaltovny velké společnosti působící ve zpracovatelském průmyslu. Jsou zde analyzovány možnosti financování investice se zaměřením na dotaci ze strukturálních fondů Evropské unie. Pomocí metod hodnocení efektivnosti investic je vybrán nejefektivnější způsob financování a formulovány vlastní návrhy a doporučení.

The thesis deals with an investment in an enamelling for big enterprise acting in the field of manufacturing industry. Possibilities of investment financing are analysed with focus on the Structural funds of the European Union. The most effective way of investment financing is chosen with the help of cost benefit analysis and therefore own suggestions and recommendations are formulated.
Efficiency Analysis of the Business Project
Keywords: Finanční analýza; investice; formy financování; zhodnocení investic; dotace; regionální politika; strukturální fondy; programovací období 2007 – 2013; operační programy; podnikatelský záměr; Financial analysis; investment; forms of financing; investment evaluation; grant; the European Union; regional policy; Structural funds; programming period 2007-2013; operational programmes; business plan